Contribution of Submicron Particles to the Unpolarized and Linearly Polarized Angular Scattering - Hu, Lianbo; Zhang, Xiaodong; Xiong, Yuanheng (Frontiers in Remote Sensing, 2022)
The scattering by suspended particles is being measured with increasing frequency in the global oceans. Yet, little is known of size fractioned contribution, particularly from submicron particles and to the polarized scattering. In this study, three Mueller scattering matrix elements, P11, P12, and P22, for the bulk particles and for size fractions <0.2 μm and <0.7/0.8 μm were measured using a commercial instrument LISST-VSF in the North Pacific Ocean in 2018 (NPO-18) and in the North Atlantic Ocean in 2021 (NAO-21). We found that P11 and P12 by particles <0.2 μm each had median value that was very similar between the two sites, even though the variability was greater in the NAO-21 than in the NPO-18. Relatively, particles <0.2 µm accounted for the same fraction of total particle scattering in P11 and P12, approximately 20% at near surface water and 40–60% at deeper depths. In contrast, P11 and P12 by particles <0.7/0.8 μm differed between the two sites, which we found was because particles of sizes 0.25–1.0 µm had greater concentration in the NAO-21 than in the NPO-18. P22 normalized to P11 indicated that the sphericity of particles was the same between submicron and bulk particles in the NPO-18 site, but bulk particles deviated more from sphericity than submicron particles in the NAO-21 site where the experiment took place during a phytoplankton spring bloom. Simulations were conducted using three particle models including homogenous spheres, mix of homogenous/coated spheres, and homogenous asymmetric hexahedra to account for the effects of particle shapes or internal structures on the polarized scattering. Using the size distribution that was measured, each of the models can reproduce some of the scattering features measured in this study, but neither of them can reproduce all. Our results suggest that accurate simulation of the polarized scattering by oceanic particles needs to account for both their nonsphericity and heterogeneity, in addition to the concentration and size distribution of the particles.